Carrying spirit in song: music and the making of ancestors at Zezuru kurova guva ceremonies - Kyker, Jennifer W. (International Library of African Music, 2009)
Among speakers of the Zezuru dialect of Shona in central Zimbabwe, the kurova guva ceremony is held roughly a year after the funeral of an adult man or woman whose spirit is said to be wandering in the bush after death without regulated ties to its kin. Kurova guva is performed to call the spirit of the deceased back from this ambiguous position, transforming it into a recognized mudzimu ancestor. Musical performance is an integral part of ritual action at kurova guva, where song is used to summon the spirit of the deceased and carry it home, transforming the wandering spirit into a mudzimu ancestor.
Keywords: African Music